Gen Z at Work: The Impact of Culture, Career Growth, and Well-being on Engagement - Anabelle, Maureen; Aryati, Ana Sofia (Jurnal Kewirausahaan dan Inovasi, 2025)
The entry of Generation Z into the workforce requires organizations to understand the factors that drive their engagement. This study aims to analyze the influence of organizational culture, career development, and employee well-being on employee engagement among Generation Z. The research employs a quantitative method with an explanatory approach. A total of 172 respondents were selected using purposive sampling, consisting of Generation Z employees in Jakarta who have worked for a minimum of six months. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The results show that all three independent variables have a positive and significant influence on employee engagement. This study contributes to a deeper understanding of engagement among the younger workforce and encourages organizations to develop HR strategies aligned with Gen Z characteristics.